Monitoring Alkalinity and Hardness During Treatment of Different Water Types - AlRubaye, Shahad F.; Al Haboubi , Naseer A.; Al-Amili , Hussein A.; Al-Allaq, Aiman H.; Rzaij , Dina R. (Al-Khwarizmi Engineering Journal, 2024)
Alkalinity and hardness are crucial factors in water treatment procedures, such as electrocoagulation (EC) and traditional coagulation–flocculation. Two types of water were employed in this study to investigate the use of EC: river water and discarded reverse osmosis system water. With bipolar and monopolar aluminum electrodes, continuous flow tests were conducted to evaluate the effects of different parameters on the variations in alkalinity and hardness versus time. The examined factors were flow rate (600 and 1,000 L/h) and number of electrodes (2 and 4). Polarity reversal was also studied. The water passed through the plates in a zigzag pattern. Results showed that the hardness under all operating conditions decreased with time, and alkalinity exhibited an oscillating behaviour. The ideal hardness removal for treating river and concentrated water was obtained using four plates with polarity reversal and a flow rate of 1,000 L/h, which were equal to 37.5% and 33.3%, respectively.